How Do Content Producers Respond to Engagement on Social Media Platforms? - Mummalaneni, Simha; Yoganarasimhan, Hema; Pathak, Varad (Marketing Science, 2026)
We examine how receiving engagement affects users’ subsequent behavior on social media platform, using a large-scale field experiment from Twitter.